Trade and Economic Growth: Theories and Evidence from the Southern African Development Community - Matias Jaime Farahane; Almas Heshmati (Global Labor Organization (GLO), 2020)
This paper empirically tests the hypothesis that trade can act as an engine of growth using panel data for the Southern African Development Community (SADC), a regional integration agreement (RIA) organization, the central objective of whose formation was the need to accelerate, foster, and encourage the region's growth. Our results indicate that during the period covered by this study (2005-2017), export expansion stimulated growth, more openness to trade reduced it, and that the formation of SADC had not yet brought about any effects on growth perhaps because of lack of full establishment of the primary instruments for achieving its central objective. These results lead to three conclusions. Firstly, trade through export expansion seems to be a better solution for SADC for achieving the central objective of its formation. Secondly, more openness to trade seems to jeopardize growth. Finally, the formation of SADC has not yet brought about the expected gains from a RIA. In this context, we recommend that policymakers should consider adopting measures aimed at supporting increased trade through promoting export expansion, achieving strong absorption of negative chocks that usually result from trade, and exploring the possibility of establishing all the planned primary instruments for achieving SADC's central objective.
Keywords: F15; F36; F43; O43; O47; 330; International trade; Regional integration agreements; Free trade area; Customs union; Prebish-Singer hypothesis